Comparative analysis of early outcomes of the first 150 cases of posterior approach robotic‐assisted radical prostatectomy and identification of the learning curve: A single‐surgeon series - Li June Tay; Henry Y. C. Pan; Leigh James Spurling; Philip Dundee (BJUI Compass, 2025)
Abstract Objectives To report intraoperative and early postoperative outcomes of posterior approach Robotic Assisted Radical Prostatectomy (RARP) patients and analyse a single‐surgeon learning curve. Patients & Methods The initial 150 patients undergoing posterior approach RARP by a single surgeon were analysed in three equal cohorts. Initial postoperative follow‐up was for a minimum of 3 months. Results A total of 150 patients were included. These cases were performed between April 2017 to June 2024. There was no significant difference in pre‐operative patient age, prostate specific antigen (PSA), body mass index (BMI), prostate volume, number of biopsy positive cores, International Society of Urological Pathologists (ISUP) grade group and clinical T‐stage. Intraoperative differences between cohorts were decreasing total operative time (153 min vs 121 min vs 106 min, p < 0.001) and estimated blood loss (296 ml vs 205 ml vs 199 ml, p < 0.001), but no difference in nerve sparing status (p = 0.243). Postoperatively, no difference was found in median length of stay, ISUP grade group, tumour volume, 30‐day readmissions or complications. There were significant differences in overall pathological T stage (p = 0.004) between the cohorts, but not positive margin status, even with T2/T3 disease. There was a significant difference in early continence recovery within the first week (p = 0.022) and at 1 month (0.041) but no difference between overall continence recovery and erectile function recovery. Conclusions Estimated blood loss and total operative time decreased across the cohorts, despite worsening disease burden. Oncological and functional outcomes are excellent throughout when compared with published literature. The learning curve may be facilitated initially by careful patient selection. Posterior approach RARP could be safely adopted by urologists adept in standard RARP, and structured training may improve the uptake of this technique.